Practice patterns and predictors of prophylactic endoscopic clip usage during polypectomy - Forbes, Nauzer; Hilsden, Robert J.; Kaplan, Gilaad G.; James, Matthew T.; Lethebe, Cord; Maxwell, Courtney; Heitman, Steven J. (Endoscopy International Open, 2019)
Background and study aims Prophylactic endoscopic clips are commonly placed during polypectomy to reduce risk of delayed bleeding, although evidence to support this practice is unclear. Our study aimed to: (1) identify variables associated with prophylactic clip use; (2) explore variability between endoscopists’ clipping practices and (3) study temporal trends in prophylactic clip use.Patients and methods This was a retrospective cohort study in a high-volume unit dedicated to screening-related colonoscopies. Colonoscopies involving polypectomy from 2008 to 2014 were reviewed. The primary outcome was prophylactic clipping status, both at the patient level and per polyp. Hierarchical regression models yielded adjusted odds ratios (AORs) to determine predictors of prophylactic clipping. Results A total of 8,366 colonoscopies involving 19,129 polypectomies were included. Polyp size ≥ 20 mm was associated with higher clip usage (AOR 2.94; 95 % CI: 2.43, 3.54) compared to polyps < 10 mm. Right-sided polyps were more likely to be clipped (AOR 2.78; 95 % CI: 2.34, 3.30) relative to the rectum. Surgeons clipped less than gastroenterologists (OR 0.52; 95 % CI: 0.44, 0.63). From 2008 to 2014, the crude proportion of prophylactically clipped cases increased by 7.4 % (95 % CI: 7.1, 7.6) from 1.9 % to 9.3 %. Significant inter-endoscopist variability in clipping practices was observed, notably, for polyps < 10 mm.Conclusions Prophylactic clip usage was correlated with established risk factors for delayed bleeding. Significantly increased clip usage over time was shown. Given that evidence does not clearly support prophylactic clipping, there is a need to educate practitioners and limit healthcare resource utilization.